Dynamic m6A mRNA Methylation Reveals the Role of METTL3/14-m6A-MNK2-ERK Signaling Axis in Skeletal Muscle Differentiation and Regeneration - Xie, Shu-Juan; Lei, Hang; Yang, Bing; Diao, Li-Ting; Liao, Jian-You; He, Jie-Hua; Tao, Shuang; Hu, Yan-Xia; Hou, Ya-Rui; Sun, Yu-Jia; Peng, Yan-Wen; Zhang, Qi; et al. (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) RNA methylation has emerged as an important factor in various biological processes by regulating gene expression. However, the dynamic profile, function and underlying molecular mechanism of m6A modification during skeletal myogenesis remain elusive. Here, we report that members of the m6A core methyltransferase complex, METTL3 and METTL14, are downregulated during skeletal muscle development. Overexpression of either METTL3 or METTL14 dramatically blocks myotube formation. Correspondingly, knockdown of Mettl3 or Mettl14 accelerates the differentiation of skeletal muscle cells. Genome-wide transcriptome analysis suggests ERK/MAPK is the downstream signaling pathway that is regulated to the greatest extent by METTL3/METTL14. Indeed, METTL3/METTL14 expression facilitates ERK/MAPK signalling. Via MeRIP-seq, we found that MNK2, a critical regulator of ERK/MAPK signaling, is m6A modified and is a direct target of METTL3/METTL14. We further revealed that YTHDF1 is a potential reader of m6A on MNK2, regulating MNK2 protein levels without affecting mRNA levels. Furthermore, we discovered that METTL3/14-MNK2 axis was up-regulated notably after acute skeletal muscle injury. Collectively, our studies revealed that the m6A writers METTL3/METTL14 and the m6A reader YTHDF1 orchestrate MNK2 expression posttranscriptionally and thus control ERK signaling, which is required for the maintenance of muscle myogenesis and may contribute to regeneration.